HUBUNGAN LINGKUNGAN SEKOLAH DENGAN MOTIVASI BELAJAR SISWA KELAS V SDN SE-KECAMATAN BUTUH TAHUN AJARAN 2019/2020 - Sri Etika Sari; Tri Saptuti Susiani; Joharman Joharman (Universitas Sebelas Maret, 2021)
Every student has different learning motivation. It is influenced by school environment. The study aimed (1) to prove positive correlation between school environment and learning motivation of fifth grade students of public elementary schools in Butuh sub-district and (2) to determine the contribution of school environment on learning motivation to fifth grade students of public elementary schools in Butuh sub-district. It was quantitative correlational study. The data collection technique was questionnaire. The sampling technique used probability cluster sampling or area sampling. The results showed that there was positive correlation between school environment and learning motivation of fifth grade students. It had strong correlation 0.556. The school environment contributed 28.58%. It concludes that there is positive relationship between school environment and learning motivation to fifth grade students of public elementary schools in Butuh sub-district in academic year of 2019/2020.